P‐128: Stress Absorbing LTPS‐TFT for Highly Flexible AMOLED. Issue 1 (2nd June 2017) - Chen, Wei-Han; Hsieh, Meng-Che; Wang, Terry Tai-Jui; Chang, Tsu-Chiang; Yang, Meng-Jung; Su, Bo-Yuan; Yeh, Yung-Hui; Ho, Jia-Chong; Chen, Glory; Tsai, Chen-Chu; Lee, Cheng-Chung
Abstract : Low temperature polycrystalline silicon (LTPS) TFT with stress‐absorbing (SA) structure for reducing the strain on a flexible polyimide (PI) substrate was successfully developed and demonstrated. It shows a good flexible TFT performance even under the bending radius of 2 mm for 100, 000 bending times.